2007
DOI: 10.1177/0021955x07079043
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Morphology of Injection Molded Structural Foams by Mold Design and Processing Parameters

Abstract: By the invention of foam processing techniques using physical blowing agents, the area of foam injection molding has caught the attention of product developers in industry as well as of researchers. Compared to conventional injection molding, the foaming approach delivers a great potential in the manufacturing as well as in the part itself, offering a monetary benefit, being vantages for example automotive and consumer goods producer (Hyde, L.J., Kishbaugh, L.A. and Katterman, J.A. (2002) [1]. How Microcellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 16 publications
1
71
0
Order By: Relevance
“…As a result, a frontal low in the core of the polymer melt is generated as shown in Figure 7. This results in a compact skin layer and a foamed core [18][19][20].…”
Section: Morphology Of Foamsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, a frontal low in the core of the polymer melt is generated as shown in Figure 7. This results in a compact skin layer and a foamed core [18][19][20].…”
Section: Morphology Of Foamsmentioning
confidence: 99%
“…It is generally deined as 0.04-0.30 g/cm 3 . Cell distances have shown that they have a deinite inluence on the mechanical properties of thermoplastic foams [16,19]. The morphology of the foam injected part can be divided into ive zones.…”
Section: Morphology Of Foamsmentioning
confidence: 99%
See 2 more Smart Citations
“…The location of the viewing windows in the fixed plate, on the opposite side of the mold cavity, makes it possible to perform various experiments by simply changing the mold insert, some of which includes, but is not limited to, gasassisted FIM studies, shear/extension induced FIM, and the study of flow in various channels. Also, the mold can be utilized to investigate other FIM technologies such as gas-counter pressure (GCP) [12,13] and mold opening (core back) [9,10,14,15]. The designed mold can be utilized to further investigate the mechanisms of bubble nucleation/growth, interaction between bubbles and fillers [16,17], the effect of formed crystals on foaming [18], weld-line studies [19], defects [20], and model verifications [21].…”
Section: Introductionmentioning
confidence: 99%